Evaluation of the Reservoir Carrying Capacity to Support the Aquaculture Activities - Annisa Novita Sari; Waluyo, Waluyo; Sri Hidayati (JFMR (Journal of Fisheries and Marine Research), 2024)
Reservoir has many functions, one of them is to support aquaculture activities. Reservoir has a limited capacity to support all of the activities in it, so, it needs to know about the carrying capacities of reservoir to support the aquaculture activities. This research was conducted on Kedungombo Reservoir, Middle of Java, Indonesia at July – August, 2023. This research used survey method to collect the primary and secondary data. Primary data collected by observation and interview. Observation used to collect data of water quality, food quantity and fish quantity, by taking 5 stations, then interpolated into 15 stations. The data about reservoir profile and its management also obtained as a secondary data. The measurement of reservoir carrying capacity used Beveridge Method (1996). The average of water quality results are temperature 29,94oC; transparency 74,80 cm; TDS 0,16 mg/l; pH 4,76; DO 8,27 mg/l; BOD 4,73 mg/l; COD 26,93 mg/l; NH3 0,1 mg/l; Nitrate 0,33 mg/l; and total phosphate 0,06 mg/l. The measurement of carrying capacity showed that the permitted amount of fish production is 1.000 tons/year, with a maximum number of floating net cages of 667. But, the existing condition in Kedungombo reservoir, there are 6.178 floating net cages with 9.267 ton/year fish productions. So, it can be concluded that aquaculture activities in the Kedungombo Reservoir have exceeded its carrying capacity.